2009
DOI: 10.1111/j.1365-2036.2009.04146.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: the effects of conservative and surgical treatment for obesity on gastro‐oesophageal reflux disease

Abstract: SUMMARY BackgroundIncidence rates of both obesity and gastro-oesophageal reflux disease (GERD) are increasing, particularly in the Western world. It has been suggested that GERD symptoms may be improved by weight reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(70 citation statements)
references
References 57 publications
1
64
0
4
Order By: Relevance
“…A 2009 review assessed the effi cacy for surgical therapies for obesity on gastroesophageal refl ux ( 95 ).…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…A 2009 review assessed the effi cacy for surgical therapies for obesity on gastroesophageal refl ux ( 95 ).…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…These varied results of weight loss on GERD symptoms could be because of small sample size, gender differences, wide variation in BMI of subjects (23 vs. 43), and use of different weight loss methods (various lifestyle changes vs. surgical approaches) (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Furthermore, a number of lifestyle intervention treatments have been attempted for GERD-low calorie diet, use of fruits/ vegetables, and physical activity; individually each intervention has no direct correlation with GERD improvement as shown in previous population-based studies (13,22,23) and a recent meta-analysis (32).…”
Section: Discussionmentioning
confidence: 99%
“…Previous data on the impact of weight loss achieved through various lifestyle (dietary changes and physical activity) (21)(22)(23)(24)(25) or surgical methods (Roux-en-Y gastric bypass or vertical band gastroplasty) (26)(27)(28)(29)(30) on GERD symptoms are scarce and with conflicting results (31). A systematic review evaluating the effects of various life style changes on GERD symptoms suggested that weight loss and head of bed elevation could improve symptoms of GERD (32).…”
Section: Introductionmentioning
confidence: 99%
“…Although weight loss and lifestyle modifications are important in reducing the symptoms of GERD, different bariatric surgeries have provided varying degrees of symptom alleviation. 17 De Groote and colleagues 17 performed a systematic review of bariatric surgery and GERD and compared the data with lifestyle modification. They found that lifestyle modification led to a decrease in GERD symptoms in 4 of 7 studies.…”
Section: Reviewmentioning
confidence: 99%